Case report: A rare case of imiquimod-induced atypical pemphigus vulgaris - Moro, Francesco; Ciccone, Davide; Fania, Luca; Mariotti, Feliciana; Salemme, Adele; Rahimi, Siavash; Pallotta, Sabatino; Di Zenzo, Giovanni (Frontiers in Medicine, 2022)
Background Pemphigus vulgaris is an autoimmune intraepithelial bullous disease involving the skin and the mucous membranes. Imiquimod, a topical therapy for skin basal cell carcinoma, is an amine that induces the production of tumor necrosis factor alfa, interleukin-1 and other cytokines. Pemphigus induced by drugs has been frequently reported, mostly after systemic therapy. Case presentation We present the case of a 50-year-old man who developed skin, intraoral, and genital mucosae lesions 3 days after a treatment with Imiquimod for multiple superficial basal cell carcinoma of the trunk. Direct and indirect immunofluorescence results were compatible with the diagnosis of pemphigus vulgaris. Enzyme-linked immunosorbent assay was negative for desmoglein 1 and 3, but interestingly, by immunoblotting on keratinocyte extracts a band of 170 kDa was obtained by IgG. The patient, after interrupting Imiquimod application, started a treatment with prednisolone and in 4 weeks showed a complete remission. Conclusion Topical Imiquimod therapy might induce atypical pemphigus vulgaris in some patients.